2018
DOI: 10.3390/ijms19041243
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxypiperidines and Their Flexible 3-(Amino)propyloxy Analogues as Non-Imidazole Histamine H3 Receptor Antagonist: Further Structure–Activity Relationship Exploration and In Vitro and In Vivo Pharmacological Evaluation

Abstract: Presynaptic histamine H3 receptors (H3R) act as auto- or heteroreceptors controlling, respectively, the release of histamine and of other neurotransmitters in the central nervous system (CNS). The extracellular levels of several neurotransmitters are enhanced by H3R antagonists, and there is a great interest for potent, brain-penetrating H3 receptor antagonists/inverse agonists to compensate for the neurotransmitter deficits present in various neurological disorders. We have shown that 1-[(benzylfuran-2-yl)met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…In previous studies on 4-hydroxypiperidines, the two ligands ADS003 and ADS009 (Figure ) were shown to be highly potent antagonists/inverse agonists at the H 3 R. They were used as lead compounds for the following structural modification: replacement of the flexible five-methylene group chain with a benzene, biphenyl, or naphthalene linker (Figure ). The idea to replace the flexible alkyl linker with semirigid groups of the lead compounds is consistent with studies that have demonstrated that replacement of the alkyl chain with more rigid moieties results in the formation of higher affinity H 3 R ligands . A moiety with a more restricted conformation may be better fitted to the receptor-binding site due to reduced flexibility (i.e., degrees of freedom) …”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…In previous studies on 4-hydroxypiperidines, the two ligands ADS003 and ADS009 (Figure ) were shown to be highly potent antagonists/inverse agonists at the H 3 R. They were used as lead compounds for the following structural modification: replacement of the flexible five-methylene group chain with a benzene, biphenyl, or naphthalene linker (Figure ). The idea to replace the flexible alkyl linker with semirigid groups of the lead compounds is consistent with studies that have demonstrated that replacement of the alkyl chain with more rigid moieties results in the formation of higher affinity H 3 R ligands . A moiety with a more restricted conformation may be better fitted to the receptor-binding site due to reduced flexibility (i.e., degrees of freedom) …”
Section: Resultssupporting
confidence: 53%
“…Previously, our laboratory has described piperazine, 40 guanidine, 41 and 4-hydroxpiperidine-based H 3 R antagonists. 42,43 The structure−activity relationship (SAR) of the 4- 2). 42,43 Further in vivo evaluation of the impact of ADS003 on brain neurotransmitter systems showed its ability to cross the blood−brain barrier and potency at H 3 R similar to the reference compound, ciproxifan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Previous studies have demonstrated that replacement of the alkyl chain with more rigid moieties such as aryl or heterocyclic rings results in the formation of highly affine H 3 R ligands. 34 Furthermore, a moiety with a more restricted conformation may be better fitted to the receptor-binding site due to reduced flexibility (i.e., degrees of freedom). 28 A key design element was to conserve the number of atoms between the phenoxy moiety and the basic nitrogen of piperazine and maintain an overall reduction in the number of rotatable bonds, thus producing more conformationally restricted compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The idea of synthesizing compounds in which the flexible alkyl chain was replaced by a semirigid aryl or cycloalkyl ring arose from our previous experiments and literature data . Previous studies have demonstrated that replacement of the alkyl chain with more rigid moieties such as aryl or heterocyclic rings results in the formation of highly affine H 3 R ligands . Furthermore, a moiety with a more restricted conformation may be better fitted to the receptor-binding site due to reduced flexibility (i.e., degrees of freedom) .…”
Section: Resultsmentioning
confidence: 99%